A Closer Look at Siblings of Patients with Schizophrenia: The Association of Depression History and Sex with Cognitive Phenotypes - Wisner, Krista M. (2010)
BACKGROUND: Siblings of patients with schizophrenia show impaired cognition and an increased prevalence of depression history. Although sex has been shown to moderate cognition in patients, this effect has not been examined in siblings. Here we elucidate how a history of depression and sex influences cognition in siblings unaffected by schizophrenia. METHODS: Unaffected siblings of patients with schizophrenia and unrelated healthy controls were evaluated neuropsychologically and completed structured clinical interviews. Participants with a depression history or no psychiatric history were selected for the sample. Cognitive performance of siblings (n = 366) and controls (n = 680) was first examined. Second, cognition of participants with a depression history and those without a psychiatric history was compared while additionally investigating the role of schizophrenia risk and sex. RESULTS: Relative to controls, siblings, with and without a psychiatric history, demonstrated significant (p < .05) cognitive deficits. Depression history impaired cognition in siblings, but not in controls; whereas sex affected cognition in both siblings and controls. In siblings alone, sex significantly interacted with depression history to influence cognition. This interaction revealed that in male - but not female - siblings a history of depression was associated with greater cognitive impairments. CONCLUSION: A history of depression impairs cognition in siblings, but not in controls. Moreover, depression history interacts with sex and demonstrates that only cognition in male siblings is significantly and additionally compromised by a history of depression. This interaction may be an important consideration for future phenotype and genetic association studies.